Effectiveness Of “Matatag Na Filipino” On Grade 9 Filipino Proficiency: A Matched-Pair Quasi-Experimental Study - Luzviminda A Parilla (Journal of Elementary and Secondary School, 2026)
This study investigated the effectiveness of the “Matatag na Filipino” supplementary material in enhancing the Filipino language proficiency of Grade 9 students at Biñan Integrated National High School. Using a matched-pair quasi-experimental design, thirty-two participants were grouped into sixteen pairs based on identical or nearly similar pre-test scores. One student from each pair was assigned to the experimental group, which utilized the supplementary material, while the other belonged to the control group, which used the standard Filipino Grade 9 module. To assess proficiency gains, participants completed pre-tests, formative tests, and post-tests. Statistical tools such as weighted mean, standard deviation, paired samples t-test, independent samples t-test, and Cohen’s d were used for analysis. Results showed that the experimental group had a pre-test mean of 15.06 and a post-test mean of 35.81, while the control group also had a pre-test mean of 15.06 but a lower post-test mean of 27.25. The paired samples t-test revealed a statistically significant improvement in both groups, with the experimental group yielding a t-value of 13.015 and the control group a t-value of 4.298. Cohen’s d indicated a very large effect size (3.36) for the experimental group and a large effect size (1.11) for the control group. The supplementary material also received a high overall acceptability rating with a mean score of 3.76, indicating strong relevance, usability, and appropriateness. These findings demonstrate that “Matatag na Filipino” is an effective tool for improving Filipino language proficiency and is recommended for broader use in secondary education